The Missing and the Missed of Lanark County, Ontario: Great War Sacrifice and the Memorialization of Exclusion in “The Volunteer” Monument - Morrison, Kelly (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
In 1923, The Volunteer monument in Almonte, Ontario was erected and dedicated to the district’s soldiers who fell in the Great War. It was designed by renowned sculptor and professor, R. Tait McKenzie, and modelled after the late Lt. Alexander George Rosamond, heir to Almonte’s esteemed Rosamond family paper mills. The seemingly simple design of a pensive bronze soldier perched atop a stone plinth, flanked by the names of his fallen comrades, is anything but simplistic in its symbolism. This article details the background, conception and realization of The Volunteer, considering the ways in which it reflects the history of the peoples who settled the region, and the collective Great War experience of Almonte and greater Lanark County. Further, in as much as the monument was specifically raised to honour the lost men of Almonte and the Township of Ramsay, this article questions whether, and in what ways, it succeeds or falters in its purpose.